Tools of promoting „energy-crops” - Kondor, Attila; Antal, József (Acta Agraria Debreceniensis, 2008)
The utilisation of renewable energy sources have come to front with the decreasing fossil fuel stocks, the unsolved problems and fears of nuclear energy and so the cumulating energy dependence. In Hungary the potential of biomass is the largest in renewable energy sources.During our examinations, we analysed the promotion of producing energy crops in Szabolcs-Szatmár-Bereg county. With the examination of the territories involved in energy crop subsidies it can be stated that the energy crop subsidy had its promoting role only on those areas where because of the bad soil conditions the energy crop producing is more profitable than other alternative (non energy) crops.The expected growth rate of energy plantations will be low, according to the low rate of subsidy intensity (40-60%). The uncertainty of direct area payments decreases the calculability that cuts back the favour of investment in short rotation forestry planting.